Non-Syndromic Recurrent Multiple Odontogenic Keratocysts: A Case Report - AR. Bartake; NG. Shreekanth; Prabhu; K. Gopalkrishnan (Tehran University of Medical Sciences, 2011)
Odontogenic keratocysts (OKCs) are one of the most frequent features of nevoid basal cell carcinoma syndrome (NBS). It is linked with mutation in the PTCH gene. Partial expression of the gene may result in occurrence of only multiple recurring OKC. Our patient presented with nine cysts with multiple recurrences over a period of 11 years without any other manifestation of the syndrome.